Analysis of Dopant Atom Distribution and Quantification of Oxygen Vacancies on Individual Gd‐Doped CeO2 Nanocrystals. Issue 21 (14th May 2014) - Stroppa, Daniel G.; Dalmaschio, Cleocir J.; Houben, Lothar; Barthel, Juri; Montoro, Luciano A.; Leite, Edson R.; Ramirez, Antonio J.
Abstract: This work reports the analysis of the distribution of Gd atoms and the quantification of O vacancies applied to individual CeO2 and Gd‐doped CeO2 nanocrystals by electron energy‐loss spectroscopy. The concentration of O vacancies measured on the undoped system (6.3±2.6 %) matches the expected value given the typical Ce 3+ content previously reported for CeO2 nanoparticles. The doped nanoparticles have an uneven distribution of dopant atoms and an atypical amount of O vacant sites (37.7±4.1 %). The measured decrease of the O content induced by Gd doping cannot be explained solely by the charge balance including Ce 3+ and Gd 3+ ions. Abstract : High‐spatial‐resolution electron energy‐loss spectroscopy is applied to map the element distribution in CeO2 and Gd:CeO2 nanocrystals. An uneven Gd dopant distribution and an abnormal increase of O vacancies were detected on the doped system (see figure). These findings indicate a possible direction to enhance transport properties in ionic conductors.